Teacher Readiness for Augmented-Reality Health Education in Elementary Physical Education: A Community-Engaged Evaluation of the BIPINIPAR Interactive Book in Surabaya - Junaidi Budi Prihantono; Dwi Lorry Juniarisca; Arifah Kaharina; Aby Nugrah Septanto; Novadri Ayubi (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Elementary physical education must translate abstract health messages about hygiene, physical activity, safety, and healthy living into concrete learning experiences. This community-engaged study evaluated BIPINIPAR, an augmented-reality interactive health-education book for Indonesian elementary Physical Education, Sport, and Health (PJOK), by examining changes in teacher readiness and perceived implementation feasibility. A one-group pre–post evaluation was conducted with 44 valid responses from elementary-school physical education teachers or education practitioners in Surabaya. Five readiness indicators were rated before and after training. Because one baseline item used a shorter scale than its paired post-training item, all readiness indicators were min–max normalized to a 0–100 metric. Program appraisal was measured with nine 1–5 items, and open-ended comments were coded thematically. Overall readiness increased from 86.14 ± 18.03 to 91.21 ± 11.94, with a mean gain of 5.08 percentage points (95% CI 1.14–9.01; p = .013; Cohen's dz = 0.39). Gains were strongest for AR-book knowledge, AR-use skill, and confidence to teach with AR. Program appraisal was very high (mean 4.81/5), with 99.5% of item-level responses in the high or very high range. BIPINIPAR is best understood as a teacher-mediated implementation-readiness intervention that can support AR-enhanced physical education, health education when accompanied by pedagogical training and sustained classroom support. Keywords: Augmented Reality, Interactive Health Education Book, Elementary Physical Education, Teacher Readiness, Community-Engaged Learning.